Connecting - Helen Walker; Sheryl Lain; Matthew B. Ittig; Laurence Musgrove; Julie O'Connell; Leslie A. Werden; Donna Souder-Hodge; Tanya R. Cochran; Rasha Diab; Thomas Ferrel; Beth Godbee (Journal of the Assembly for Expanded Perspectives on Learning, 2016)
Helen Walker - More Apt, Connected Title Sheryl Lain - Hey, Teach! Do You Love Me? Matthew B. Ittig - Ask Me Tomorrow Laurence Musgrove - Writing Program Julie O’Connell - The Power of a Slave Narrative Leslie A. Werden - Embracing Chaos Donna Souder-Hodge - Teaching Dachau Tanya R. Cochran, Rasha Diab, Thomas Ferrel, & Beth Godbee - Hanging Out: Cultivating Life-Giving Writing Groups Online